Diversity of Insects in different peatland ecosystem - Sherone Caroline, U.Oboi (Universiti Malaysia Sarawak, UNIMAS, 2013)
A study of insect diversity in different peatland ecosystem was held in Betong Division, Sarawak. The sampling takes place in four different peatland ecosystem, which represent the least disturbed peat swamp forest (Maludam National Park), disturbed peat swamp forest by being closed to long house and cultivated area (Tanjung Baru Forest), logged over peat swamp forest (Cermat Ceria Forest) and peat swamp forest that had been converted to oil palm plantation (Durafarm Oil Palm Plantation). Light trap method had been used to collect the sample of nocturnal insect for two hours in each site. A total of 13 order of insects that represented 176 species of insects have been collected in these four different sampling sites. In this study, the total number of species caught in oil palm plantation was higher compared to the peat swamp forest. The Shanon’s diversity index was computed using PAST programme. The diversity index shows that Durafarm Oil Palm Plantation has higher diversity compared to other sites. Meanwhile, Tanjung Baru Forest which represents the disturbed peat swamp forest by closed to long house and cultivated area has the lowest diversity. Zar t-test shows that there were significant differences between these four sites. Five species of insects were most affected by the conversion of forest to oil palm plantation and two species of insects were least affected by this conversion.